Pemetaan Lokasi Rawan Kecelakaan Lalu Lintas Menggunakan Sistem Informasi Geografis - Irsan, Laode Muhamad; Hasanah, Nur; Musyawarah, Rahma; Garusu, Ema Hermawati (PT. Pubsains Nur Cendekia, 2024)
Traffic accidents often result in death and serious injury. This high number of deaths and injuries requires immediate action to reduce the negative impact. This study aims to identify and map the location of traffic black sites in the districts of Konda and Wolasi. This research was conducted on the main road in the South Konawe regency which had an accident on the Konda-Wolasi route. The research method used to determine accident-prone locations is the Z-Score method, while to find accident-prone maps, spatial analysis is used using geographic information systems through field surveys and plotting coordinates by GPS. In the Konda sub-district, 4 villages are accident-prone points, namely Ambololi, Lambusa, Puuosu Jaya, and Tanea villages, while in the Wolasi sub-district, there are Wolasi, Mata Wolasi, Amoito, and Leleka sub-district. Each accident-prone point caused damaged roads, narrow roads, bends, and intersections.